A Intermitência Histórica E O Lugar Da Filosofia No Currículo Médio Paulista No Período De 1961 A 2008 - Furtado Filho, Verissimo Dos Santos [UNIFESP] (2018)
The Proposal Of This Research Is To Investigate Which Is The Place Of The Philosophy Discipline In The Curriculum Of High School In São Paulo. For That, It Takes As Its Starting Point Its Institutionalization As A School Discipline, Defining, From The Concepts Of Some Renowned Thinkers, What Becomes A School Discipline, Pointing Out The Positive And Negative Effects Of Instrumentalizing Philosophy As A Discipline. From Its History As A Discipline, In The Period Delineated (1961-2008), The Factors Determining Its Presence Or Absence In The Brazilian (Generally) And São Paulo (Especially) School Curriculum Are Analyzed. In The Meantime, The Changes In Education During The Military Period, The Near Extinction Of The Philosophy Of The School Curriculum, The Struggle For Its Reintroduction In The Curriculum, The Participation Of Institutions, Teachers And Students Of São Paulo In This Battle, The Clashes Between The Legislative And The Executive Power Of São Paulo Around Philosophy Doing Or Not Part Of The Average